IMPLEMENTASI STRATEGI E-MARKETING BERBASIS WEB (STUDI KASUS: PERUSAHAAN KATERING DAN DEKORASI) - S Pasaribu, Johni; Taryanto, Ardi (Politeknik Dharma Patria Kebumen, 2018)
The purpose of research is to produce a model of e-marketing strategies in order to identify the existing problems faced by the company and to identify its weaknesses. Additionally, this research designs a web based Marketing system. The development of the Internet improvethe way of doing business from traditional to electronic, no denying that the economic activity leading to the marketing of electronic. The system has been designed to give facilitation for customer to get information abaut material of tutorial activity fast and efficient. The methodologies used are literature study, observation, interview, analysis and design with seven-stages marketing internet. It is concluded that e-Marketing system that has been designed supports information access easily and fast. The e-Marketing application consists of features such as Online Register, Contact us, Download, News, and Complaint. It is expected to help deliver and maintain customer satisfaction by building a close relationship to the customers.